Tennison-Randall Repair of Cleft Lip Without Calipers. Issue 2 (June 2022) - Parsa, Fereydoun D.; Singh, Dylan; Parsa, Alan A.
Background: Over many years of teaching cleft lip repair, we observed that plastic surgery students often find the principles of skin markings and incisions difficult to conceptualize. The approach described in this report designed and presented as our preferred approach in mitigating this difficulty.Methods: Over a period of 40 years a large number of cleft lips were repaired both in the United States as well as abroad. Both the Millard and Tennison-Randall approaches were utilized by the senior author (FDP). However, skin markings and the use of a template, as reported in this study, were found to communicate the concept and principle of cleft lip repair better than other previously utilized approaches.Results: We found that the students of plastic surgery easily understood and assimilated the principles of cleft lip repair when the initial markings and the execution of incisions were carried out "free-hand" without calipers and with the help of a template.Conclusions: The approach used in this report is proposed as a means of communicating the essential principles of cleft lip repair to students of plastic surgery who are initially exposed to this congenital anomaly.